THE MUTATIONAL PROFILE OF THE ATP7B GENE IN WILSON'S DISEASE: TOWARDS A MUTATION CENTRIC MOLECULAR DIAGNOSTIC STRATEGY - Oumaima OUTANI (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2023)
Wilson disease (WD) is a multisystem autosomal recessive disorder that impairs copper metabolism, and it can be treatable with pharmacological agents. Prognosis in this disease is generally favorable in the case of early diagnosis and early treatment. Moreover, genetics is an important step in diagnosis and family screening. Our study aims to describe the clinical manifestations of WD, assess the mutational status of the ATP7B gene, and investigate potential phenotype-genotype correlations. Additionally, we aim to contribute to the growing understanding of the mutational landscape, which could enhance genetic diagnostic strategies and patient outcomes. Using Next Generation Sequencing (NGS), we identified five distinct mutations in our cohort. Patient 1 had two compound heterozygous mutations c.3664delG and c.3244-2A>G, while patients (2, 3, and 4) exhibited homozygous mutations. Patient 2 was positive for the c.2507G>A mutation, patient 3 had the c.865C>T mutation, and patient 4 carried with the c.3059A>G mutation. Based on these genetic epidemiological findings and previous Moroccan studies, we proposed an optimized diagnostic strategy that may alleviate financial hardships for patients seeking WD diagnosis by reducing the cost and wait-time involved with NGS. The suggested strategy involves an initial screening for the two prevalent Moroccan mutations we identified, c.865C>T (p.Gln289Ter) and c.2507G>A (p.Gly836Glu), using cost-effective techniques like Sanger sequencing. If these mutations are not detected, NGS can be considered for in-depth analysis.
Keywords: Wilson; Next Generation Sequencing; Sanger; Morocco; Strategy